MANAJEMEN KRISIS TVRI DI ERA MILENIAL - Maimun Hasballah; Wakidul Kohar; Maskota Delfi (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
This article discusses TVRI's understanding of the crisis it faces and how crisismanagement is carried out to deal with the crisis. The crisis faced by TVRI was a crisis related to the management of the organization, especially related to finance and HR, and the reputation crisis because the image as a old school TV attached to TVRI that arose because of changes in the audience as recipients of messages was not followed by changes to TVRI as a communicator. TVRI management takes steps to adapt to the changes that have occurred in this millennial era. The steps taken are communicated into and out of the institution using the current media to get support from the internal and attract public attention.